CP-219 Assessment of the appropriateness of prescriptions of clotting factors complex (OCTAPLEX) and fibrinogen (CLOTTAFACT) in a university hospital. (25th February 2017) - Delforge, M; Marchand, M; Massip, P; Lefevre, S; Cestac, P; Condat, B Juillard
Abstract : Background: In 2015, Octaplex and Clottafact were identified among the most prescribed medications with a high financial impact in the university hospital. Expenses for those drugs increased respectively by 10% (+€23 900) and 14% (+€239 300) in 2015. Purpose: The aim of the study was to evaluate the appropriateness of Octaplex and Clottafact prescriptions to see if this increase was justified. Material and methods: We audited the prescriptions made in the first quarter of 2016 with a set of criteria based on these medications' indications. Those criteria were divided in 3 groups: conformity of the prescription with regulatory demands (group 1), for example (IE) was there a computerised traceability of the medication's prescription? Relevance of the prescription regarding patient biological (group 2) and clinical (group 3) data. We assigned a score for each criterion, weighted to reflect its importance. The sum of scores then gave each prescription a letter, characterising their appropriateness. The letters were: A=appropriate, B=intermediately appropriate and C=inappropriate. This method was approved by physicians and pharmacists, and members of the commission for medicines of the hospital. Results: 16% (44/272) of prescriptions were audited: 28% (14/111) were for Octaplex and 19% (30/161) for Clottafact. Group 1: 50% of prescriptions were classified as A (22/44), 36% (16/44) were B and 14% (6/44) were C. only 34% (15/44) were computerised. Group 2: 54% were classified as A (24/44), 41% (18/44) were B and 5% (2/44) were C. For 37% (11/30) of fibrinogen prescriptions, there was no hypofibrinogenaemia. Group 3: 75% (33/44) were classified as A, 20% (9/44) were B and 5% (2/44) were C (for those 2 prescriptions, there was no mention of bleeding or blood transfusion in the patients' records). Conclusion: 25% (11/44) of the prescriptions were appropriate, 72% (32/44) were intermediately appropriate and 3% (1/44) seemed inappropriate. This is acceptable considering that these medications are usually administered in emergencies, when staff have to think and act fast. These results have been presented to the prescribers with a reminder of those medicines with indications of a 'last resort' character. This type of audit will be renewed periodically, the set of criteria being adaptable to any medication. No conflict of interest